Tujuan Pendidikan Islam Perspektif Quraish Shihab: Era Digital - Armedi, Rama (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2024)
This research aims to analyze the concept of education in surah Al-Baqarah verse 30 towards the objectives of Islamic education in the digital era from the perspective of M Quraish Shihab. This research was conducted using a library research approach, which collects data through books, scientific articles, journals, and written sources that aim to obtain in-depth analysis related to research studies. The results showed that the concept of the Qur'an Surah Al-Baqarah verse 30 in the perspective of M. Quraish Shihab emphasizes fostering humans personally and in groups so that they are able to carry out their functions as servants and caliphs who emphasize human responsibility as representatives of Allah on earth, forming the goals of Islamic education that develops moral character, social responsibility, intellectual competence. Islamic education must integrate spiritual values with the development of science and technology to prepare students who are able to become leaders who contribute positively to society.